PLAGIOSTACHYS STROBILIFERA VAR. CONICA (ZINGIBERACEAE), A NEW VARIETY FROM SARAWAK, BORNEO - Salasiah Mohamad; Meekiong Kalu (BRIN Publishing (Penerbit BRIN), 2020)
SALASIAH, M. & MEEKIONG, K. 2020. Plagiostachys strobilifera var. conica, a new variety from Sarawak, Borneo. Reinwardtia 19(2): 109‒116. ‒‒ The new taxon varies from Plagiostachys strobilifera var. strobilifera in the broader lanceolate leaves, the bilobed ligule, the longer calyx, the rounded anther crests, the oblong lateral staminodes, and the non-free apical bracteole with conical apex (which gives the taxon its epithet). A key to species of Bornean Plagiostachys is also provided, along with a conservation assessment.